2018
DOI: 10.1364/oe.26.005591
|View full text |Cite
|
Sign up to set email alerts
|

Development of high performance green c-plane III-nitride light-emitting diodes

Abstract: The effect of employing an AlGaN cap layer in the active region of green c-plane light-emitting diodes (LEDs) was studied. Each quantum well (QW) and barrier in the active region consisted of an InGaN QW and a thin AlGaN cap layer grown at a relatively low temperature and a GaN barrier grown at a higher temperature. A series of experiments and simulations were carried out to explore the effects of varying the AlGaN cap layer thickness and GaN barrier growth temperature on LED efficiency and electrical performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 33 publications
1
34
0
Order By: Relevance
“…Tremendous efforts have been done to improve the efficiency of GaN-based LEDs, which can be principally divided into two categories: improving the crystal quality of epilayer [6,7,8,9,10] and boosting the light extraction efficiency (LEE) [11,12,13,14,15]. Since mini-LEDs are obtained from the identical epilayer as broad-area LEDs, the fruitful methods for high crystal quality epilayer are universal in fabrication of the two kinds of LEDs.…”
Section: Introductionmentioning
confidence: 99%
“…Tremendous efforts have been done to improve the efficiency of GaN-based LEDs, which can be principally divided into two categories: improving the crystal quality of epilayer [6,7,8,9,10] and boosting the light extraction efficiency (LEE) [11,12,13,14,15]. Since mini-LEDs are obtained from the identical epilayer as broad-area LEDs, the fruitful methods for high crystal quality epilayer are universal in fabrication of the two kinds of LEDs.…”
Section: Introductionmentioning
confidence: 99%
“…The bright luminous area in InGaN QWs by PL measurements was expanded using optimal high growth rate conditions. Alhassan et al also reported the highly efficient green LEDs using the high growth rate (6 nm/min) for InGaN QWs [58]. Therefore, a high growth rate of high-In-A c c e p t e d M a n u s c r i p t 10 content InGaN QWs is effective to improve the crystal quality.…”
Section: Growth Ratementioning
confidence: 99%
“…Ultraviolet (UV)-emitting group III-nitride materials hold a promising potential for a variety of multifunctional applications, including solid-state lighting technology [1][2][3][4] and water purification and disinfection [5,6] . With the wide range of wavelength tunability available to UV-emitting group III-nitride materials, the most promising germicidal ultraviolet devices are found in aluminum gallium nitride and its alloys (Al x Ga 1−x N, where 0 < x < 1), and one of the most crucial applications of Al x Ga 1−x N-based devices is water sterilization [7][8][9][10] , particularly for highly water-stressed countries.…”
Section: Introductionmentioning
confidence: 99%
“…Nagasawa and Hirano argued that the low TDDs of roughly 5 × 10 8 cm -2 demonstrated by Al x Ga 1−x N and AlN templates on sapphire decreases the number of nonradiative recombination channels [127] . γ While it has been well established that electron-beam irradiation [91] and thermal processing [128] can activate dopant impurities in In x Ga 1−x N and remove magnesium-hydrogen complexes in GaN films [129] , this raises the following questions: (1) If an electron-beam can ionize impurities in In x Ga 1−x N, can one develop an in-situ ion activation system for the growth of Al x Ga 1−x N [130][131][132][133] ? (2) During the epitaxial growth process, can one irradiate the sample with UV, X-ray, or, perhaps,ray radiation?…”
mentioning
confidence: 99%